2021
DOI: 10.3390/electronics10232913
|View full text |Cite|
|
Sign up to set email alerts
|

A Shared Cyber Threat Intelligence Solution for SMEs

Abstract: Small- and medium-sized enterprises (SMEs) frequently experience cyberattacks, but often do not have the means to counter these attacks. Therefore, cybersecurity researchers and practitioners need to aid SMEs in their defence against cyber threats. Research has shown that SMEs require solutions that are automated and adapted to their context. In recent years, we have seen a surge in initiatives to share cyber threat intelligence (CTI) to improve collective cybersecurity resilience. Shared CTI has the potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…Finally, Haastrecht et al [7] showed how small and medium size enterprises suffer from the lack of CTI tools and shared information. They created a CTI Feed that can provide these companies with actionable recommendations that are ordered by relevance and helped them avoid vulnerabilities and threats.…”
Section: Cti Main Challenges and Technical Improvementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Haastrecht et al [7] showed how small and medium size enterprises suffer from the lack of CTI tools and shared information. They created a CTI Feed that can provide these companies with actionable recommendations that are ordered by relevance and helped them avoid vulnerabilities and threats.…”
Section: Cti Main Challenges and Technical Improvementsmentioning
confidence: 99%
“…It is known that CTI must explore the collection while filtering, sharing and analyzing vulnerabilities in intel and threat data regardless of vendor, technology or source. For that, much research has been developed to address the collection and filtering of threat intelligence [4,5], as well as sharing and using that data to mitigate threats [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, SMEs do not budget adequately for cybersecurity solutions such as purchasing products, services, and external consulting services. It is suggested that the government subsidise certain funding to assist SMEs in improving their cybersecurity posture, providing tools to reduce the cost of IT solutions based on effective procurement methods, and many other things (Tamyez, 2022;van Haastrecht et al, 2021). For example, after negotiation and consideration of authority, SMEs can subscribe to customised Service Legal Agreements (SLA) based on their size and suitability to fit SMEs cybersecurity needs.…”
Section: Solutions For Cybersecurity Among Smes Companiesmentioning
confidence: 99%
“…Other efforts focusing on the automatic collection and processing of can be found in the works of [13] and [14], where Indicators Of Compromise (IOCs) are extracted from the corresponding data. To both process and analyse the collected data, the authors of [15] propose a solution that processes Malware Information Sharing Platform (MISP) data automatically, prioritizes cybersecurity threats for Small and medium-sized enterprises (SMEs), and provides SMEs with actionable recommendations tailored to their context. On top of solutions like the ones mentioned above, in order to facilitate the automation of processes regarding the CTI, standardization efforts have been made.…”
Section: B Related Workmentioning
confidence: 99%